Characterisation of the 3'-UTR of the COL5A1 gene: implication for musculoskeletal soft tissue injuries - Laguette, Mary-Jessica Nancy (MRC/UCT RU for Exercise and Sport Medicine, 2015)
COL5A1 encodes the α1 chain of type V collagen, a minor fibrillar collagen that is an important regulator of collagen fibril assembly. A polymorphism (rs12722, C/T) within the 3'-untranslated region (UTR) of COL5A1 is associated with chronic Achilles tendinopathy (TEN) and other soft tissue injuries as well as exercise-related phenotypes. These phenotypes are directly or indirectly associated with the mechanical properties of musculoskeletal soft tissue. It has therefore been hypothesised that variants in the COL5A1 gene, specifically the 3'-UTR, regulate synthesis of the α1(V) chain and type V collagen production. Type V collagen levels in turn regulate fibril architecture and structure and, thereby, mechanical properties of musculoskeletal soft tissues. Although the 3'-UTR of many eukaryotic genes have been shown to play an important regulatory role, the function of the COL5A1 3'-UTR is currently unknown. Aim. The primary aim of this thesis was therefore to determine whether the COL5A1 3'-UTR was functional and to identify functional differences between the COL5A1 3'-UTR cloned from participants with TEN and healthy asymptomatic control individuals. The secondary aim was to start mapping the functional regions within the 3'-UTR, focusing on regions which are potentially responsible for contributing to the tendinopathic phenotype.